SINTESIS α-TERPINEOL DARI MINYAK ATSIRI TUMBUHAN SAPU-SAPU DENGAN MENGGUNAKAN KOMBINASI KATALIS ASAM ALAMI BUAH JERUK KUNCI DAN ASAM SINTETIS - Ependi, Eresti; Roanisca, Occa; Nurhadini, Nurhadini (Department of Chemistry - Universitas Bangka Belitung, 2025)
Synthesis is an integration of two or more existing elements to produce a new result. Key orange (Citrus x microcarpa Bunge) is a Bangka Belitung plant that contains citric acid with a high acidic taste. Its high acidic nature can be used as a catalyst that can accelerate the reaction rate in synthesizing an α-terpineol compound from α-pinene contained in broomstick essential oil. The synthesis of α-terpineol can be done using combined and uncombined catalysts, namely 15% sulfuric acid, 99.5% acetic acid and natural citric acid from key lime juice. This study aims to determine the optimum composition of the catalyst combination of sulfuric acid, acetic acid and key lime juice in synthesizing α-terpineol compounds and the level of α-terpineol produced from the synthesis. The optimum result of the combination of catalysts that can synthesize α-pinene into α-terpineol quite well is using 15% sulfuric acid as much as 1 ml, 99.5% acetic acid as much as 1 ml and citric acid from key orange juice as much as 3 ml. The results of α-terpineol content of each catalyst are Product 1 by 33.14%, Product 2 by 6.36%, Product 3 by 1.00%, Product 4 by 17.32% and Product 5 by 18.43%.